Efectiveness of Implemenying Qris Transacyion In Pandemic Covid-19 - Hartono Subagio (Journal Research of Social Science, Economics, and Management, 2023)
The purpose of this study is to study how widely QRIS is used among micro, small and medium enterprises (MSMEs) and how effective QRIS is in transaction processing. Reviewing the experiences of buyers and owners of micro, small and medium enterprises (MSMEs) having used QRIS has outlined the best way to use the system. This study uses a qualitative descriptive methodology. The goal of qualitative research is to bring researchers and the phenomena they study closer together in an interactive process that increases everyone's knowledge. While describing a phenomenon and its characteristics is the main goal of descriptive research. Observations, interviews, and documentation will be used to collect data, which will then be analyzed to provide solutions to the problems formulated and draw conclusions. The research findings show that first, many merchants and the general public do not understand the features and advantages of the program, the installation of a QRIS-based payment gateway for merchant transactions is still not going well. Second, the community and MSME actors are starting to switch to using QRIS because it can minimize the spread of Covid-19. Third, QRIS shows effectiveness in the transaction process during the Covid-19 pandemic which was very effective, besides that there are 2 types of transaction mechanisms using QRIS, the first is Merchant-Presented (push payment) and Customer-Presented (pull payment).